Evaluation of the Efficacy of the VHO-Osthold® Perfect Orthonyxic Buckle While Treating Ingrown Nails and Its Effect on the Clinical Picture of the Nail Apparatus - Kuros, Faustyna; Wcisło-Dziadecka, Dominika (Applied sciences, 2023)
Background: An ingrown nail (IN—ingrowing nail) is a very troublesome condition that mainly affects the big toe in all age groups and involves the ingrowth of part of the nail plate into the soft periungual tissues, causing an inflammatory reaction, pain, and even a bacterial infection. As a result of the evolution of inflammation, highly vascularized and painful granulation tissue is formed, visible in the side walls, which causes difficulties in walking, while reducing the quality of life of patients in everyday functioning. The aim of the study was to evaluate the effectiveness of the VHO-Osthold® Perfect orthonyxic buckle while treating ingrown nails and its effect on the clinical picture of the nail apparatus. Methods: A prospective observational study was conducted on 39 patients with ingrown toenails in Scholz stage 3a–5b who underwent therapy with the use of a VHO-Osthold® Perfect orthonyxic brace. An original questionnaire form was used to assess the therapy, consisting of several parts concerning the type and stage of the ingrown nails, the location and aetiopathogenesis of the ingrown nails, pain, and the patients’ life quality before and after therapy. Results: All elements improved significantly after treatment (p < 0.05 each). Twelve months after the end of therapy, none of the probands reported disease relapse. The predominant location of ingrown nails was both big toes (69.2% for each foot). The most common group of reasons was outer pressure—all patients experienced at least one issue, with frequent mechanical injuries being the most common (59.0%), followed by wearing too-small shoes (46.2%). Almost half of the patients declared no worries during treatment (48.7%). Life quality assessment grew from 1.82 ± 1.02 to 6.41 ± 0.72 on a scale from 1 to 7, p < 0.001. Conclusions: The VHO-Osthold® Perfect clamp eliminates pain after application to the ingrown toenail and allows for a safe and conservative approach to the treatment of ingrown toenails, improving the clinical picture of the nail apparatus, general well-being, and the quality of life of patients with advanced ingrown toenails.